PENGARUH MODEL PEMBELARAN BEBASIS PROYEK TEHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA PADA MATERI FLUIDA STATIS - Sumardiana Sumardiana; Asrorul Azizi; Muh. Zaini Hasanul Muttaqin (JURNAL ILMIAH GLOBAL EDUCATION, 2021)
This study aims to determine the effect of the PjBL learning model on students' problem-solving abilities on the material of Static Fluids at MA Sabilurrasyad in Class XI MIA 1 and XI MIA II. The type of research used is a quasi-experimental which aims to determine the problem solving ability of students who learn to use PjBL and conventional models. Data analysis was obtained from the results of the pretest and posttest of students using SPSS. Based on the results of the one-way ANOVA analysis, F-count 182.34 was obtained with a P-value (0.000 < 0.05) which means that there is a very significant difference in problem solving ability between the experimental class and the control class. The percentage score of problem solving ability at the logical solution level is 50% in the experimental class. While the percentage in the control class at the level of students' logical physics solutions is 0%. Students still have difficulty at the stage of connecting some physics concepts and determining solutions.